Catheter ablation of ventricular arrhythmia guided by a high‐density grid catheter. (20th January 2020) - Campbell, Timothy; Trivic, Ivana; Bennett, Richard G.; Anderson, Robert D.; Turnbull, Samual; Pham, Timmy; Nalliah, Chrishan; Kizana, Eddy; Watts, Troy; Lee, Geoffrey; Kumar, Saurabh
Abstract: Introduction: Minimal data exist on the Advisor HD Grid (HDG) catheter and the Precision electroanatomic mapping (EAM) system for ventricular arrhythmia (VA) procedures. Using the HDG catheter, the EAM uses the high‐density (HD) wave mapping and best duplicate software to compare the maximum peak‐to‐peak bipolar voltages within a small zone independent of wavefront direction and catheter orientation. This study aimed to summarize the procedural experience for VAs using the HDG catheter. Methods: Clinical and procedural characteristics of VA ablation procedures were retrospectively reviewed that used the HDG catheter and the Precision EAM over a 12‐month period. Results: A total of 22 patients, 18 with sustained ventricular tachycardia and 4 with premature ventricular contractions were included. Clinically indicated left and/or right ventricular (LV, RV, respectively), and aortic maps were created. LV substrate maps (n = 13) used a median 1700 points (interquartile range [IQR]25%‐75%, 1427‐2412) out of a median 18 573 (IQR25%‐75%, 15 713‐41 067) total points collected. RV substrate maps (n = 11) used a median 1435 points (IQR25%‐75%, 1114‐1871) out of a median 16 005 (IQR25%‐75%, 11 063‐21 405) total points collected. Total point utilization, used vs collected, was 9%. Mean mapping time was 43 ± 17 minutes (substrate, 34 ± 18 minutes; activation/pace mapping, 9 ± 13 minutes). Acute success was achieved in 56 (86%) and short‐term success achieved in 16 patients (73%) at a median follow‐up of 145 days (IQR25%‐75%, 62‐273 days). There were no procedural complications. Conclusion: HD wave mapping using the novel HDG catheter integrated with the Precision EAM is safe and feasible in VA procedures in the LV, RV, and aorta. Mapping times are consistent with other multielectrode mapping catheters.